CFD modelling of air quality in Pamplona City (Spain): Assessment, stations spatial representativeness and health impacts valuation - Rivas, Esther; Santiago, Jose Luis; Lechón, Yolanda; Martín, Fernando; Ariño, Arturo; Pons, Juan José; Santamaría, Jesús Miguel (My University, 2024)
A methodology based on CFD-RANS simulations (WA CFD-RANS, Weighted Averaged Computational Fluid Dynamic-Reynolds–Averaged Navier–Stokes simulations) which includes appropriate modifications, has been applied to compute the annual, seasonal, and hourly average concentration of NO2 and NOX throughout the city of Pamplona (Spain) at pedestrian level during 2016. The results have been evaluated using measurements provided both by the city's network of air quality monitoring stations and by a network of mobile microsensors carried around by cyclists during their daily commutes, obtaining a maximum relative error lower than 30% when computing NO2 annual average concentrations. The model has taken into account the actual city layout in three dimensions, as well as the traffic emissions. The resulting air pollution maps provided information critical for studying the traffic-related health effects of NO2 and their associated external costs in the city of Pamplona and the spatial representativeness of the current network of air quality monitoring stations (it has not been carried out for an entire city to date). The developed methodology can be applied to similar cities, providing useful information for the decision-makers.
Keywords: CFD model; city scale; NO2 health effects; spatial representativeness of monitoring; urban air quality